Advanced penetration testing for highly-secured environments : the ultimate security guide : learn to perform professional penetration testing for highly-secured environments with this intensive hands-on guide /: the ultimate security guide : learn to perform professional penetration testing for highly-secured environments with this intensive hands-on guide. (2012) - Unknown
No abstract available